Plasma Sterilization Effectively Reduces Bacterial Contamination in Dental Unit Waterlines - Sarocha Noopan; Phattranit Unchui; Supitcha Techotinnakorn; Ruchanee Salingcarnboriboon Ampornaramveth (International Journal of Dentistry)
Objective. To investigate the effectiveness of plasma sterilization in reducing bacterial contamination and controlling biofilms in dental unit waterlines. Materials and Methods. Ten identical dental chair units (DCUs) were used. Five DCUs were installed with an automated plasma sterilization system (PSS) and the other five were kept as nontreated controls (CTL). Water flushed from the airotor line served as the output water of the dental unit waterlines (DUWLs). Water samples were collected at the beginning and on a weekly basis for 4 months. Water was analyzed for bacterial contamination (CFU/mL). Scanning electron microscopy (SEM) was used to investigate the amount of biofilm in the waterlines. Biofilm viability was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assays. All statistical analyses were performed using the Mann–Whitney U test. A value of p<0.05 was considered significant. Results. The DCU output water was found to be heavily contaminated with bacteria. Plasma sterilization effectively reduced bacterial contamination from an average of 212 CFU/mL to 8 CFU/mL. During the entire period of 4 months, the level remained below 500 CFU/mL, the standard level recommended by the Centers for Disease Control and Prevention (CDC) of the USA. The reduction in the bacterial count was significant compared with the CTL group (p<0.05). Plasma sterilization could not eradicate the existing biofilms in the waterlines, and it did reduce biofilm mass and viability. Moreover, treatment with plasma sterilization did not induce a change in the composition of microorganisms, as analyzed by Gram staining. Conclusion. Plasma sterilization, which is part of electrochemically activated water, effectively reduces bacterial contamination and reduces biofilms in dental unit waterlines.